EFFECT OF CUSTOMER’S OVERALL OUTLLOOK TOWARDS GREEN BANKING PRACTICES - Devi, M. Deepthi Varsha; K. Uma (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The present research aims to explore the connection between the socioeconomic backgrounds of respondents and their awareness levels as bank customers. It will also investigate the relationship between their awareness and customer opinions, along with the various factors that shape customer perspectives on green banking practices. Primary as well as secondary sources of data are used in this research. In the Madurai district, information was gathered from customers of the three leading public sector banks: State Bank of India, Bank of Baroda, and Canara Bank. Convenience sampling is used to choose 200 respondents for the study, which fills a research gap. The RBI website, scholarly journals, and the annual reports of different banks were the sources of secondary data. The research employed statistical methods including reliability testing, frequency analysis, factor analysis, independent T-tests, and correlation analysis. The analysis identified seven factors influencing customer opinions on green banking: security, responsibility, sustainability, eco-consciousness, ease of use, accessibility, and availability.